Financial development in South Africa: The role of natural resources, IT infrastructure, and government size - Paul Adjei Kwakwa; Justice Boateng Dankwah; Emmanuel Adu Boahen; Paul Hammond (Cogent Economics & Finance, 2023)
The purpose of this paper is to identify the driving elements of the South African financial sector. While South Africa's financial sector appears robust, there exists a dearth of empirical research investigating the determinants of its development. Thus, this work assesses how three critical factors: natural resource abundance (NR), IT infrastructure, and government expenditure levels affect financial development (FD) in South Africa using annual data from 1971 to 2020. Preliminary findings show that the series are integrated, and they are cointegrated. Results from regression analysis suggest that the abundance of NR does not significantly contribute to financial development in South Africa. Conversely, advanced IT infrastructure, larger government size, and openness to trade are associated with a more developed financial sector. The implications of these findings are essential for policymakers and stakeholders in understanding the factors that drive financial development in South Africa. The study recommends that, among others, innovative approaches are needed to channel gains from natural resources effectively into the financial sector.
Keywords: 330; financial development; government size; infrastructure; natural resources rent; South Africa